KESOPANAN BERKOMUNIKASI DALAM ASPEK KONSEP WAJAH - Abd. Rahman (Kantor Bahasa Kalimantan Timur, 2016)
Speaking is a means of social interaction. Through language, someone can share ideas and thoughts to the hearer. This interaction process needs an understanding between the speaker and the hearer. The speaker should understand the concept of face in social interaction so that the communication process can run well. The object of this research is George Yule’s concept of face. This concept is about self-image that should be taken into account by the hearer. Face will be constructed differently based on the situations. The analysis uses descriptive qualitative method. Qualitative method provides a lot of data from the social community. Then, the data are constructed in a theme that has meaning and is easily understood. The knowledge of face concept in social interaction helps us to see hearers’ thought and direction of the talk even though without any words stated.